Academic Stress Scale: Contruction And Psychometric Analysis - Sodiq, Fajar; Husna , Aftina Nurul; Hermahayu (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Stress is part of the psychological that can be experienced by every individual. Stress experienced by students towards activities or situations in higher education can be referred to as academic stress. Students who experience extreme stress can have an unfavorable effect on the learning process and student achievement. This study aims to develop a student academic stress scale. The scale preparation in this research was based on 4 aspects of academic stress, namely: cognitive, affective, physiological and behavioral. In this research, data was obtained by distributing the academic stress scale that is being developed using a simple random sampling technique. The validity test was carried out by referring to Aiken's V formula (v 0.70) and the reliability test using the Alpha Cronbachs internal consistency method (rXY 0.3). Based on the try-out test with N82 (30 students and 52 female students), the value of 0.943 was obtained with 36 final items, consisting of 18 favorable items and 18 unfavorable items. There are still shortcomings in the results of this research, such as the final items which are still quite large, so in the next research it is hoped that it can be tested again on a larger sample to increase the reliability and validity of this academic stress measuring tool.